(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Distillation is one of many processes available for water purification, and sunlight has heat energy that can be used to power that process. Sunlight has advantage of zero fuel cost but it available in attuned format so requires larger collector areas i.e. absorber surfaces due to this it becomes costlier equipment. It is misnomer that for distillation we need to boil water actually simply elevating its temperature, short of boiling will adequately increase the evaporation rate. In fact, although vigorous boiling hastens the distillation process it also can force unwanted residue into the distillate, defeating purification. To boil water with sunlight requires more costly apparatus than is needed to distill it little more slowly without boiling. Different levels of purification can be achieved with this equipment which can be used for sterilized water for medical uses. Purification of heavy water in dissolved salts differs from purification of water that has been dirtied by other chemicals processes.